The Mamlukization of the Mamluk Sultanate? State Formation and the History of Fifteenth Century Egypt and Syria: Part I — Old Problems and New Trends - Steenbergen, Jo van (History compass, 2016)
This is the first of two connected articles that aim to offer a new perspective on the history of late medieval Egypt and Syria, on 15th-century political history of the so-called Mamluk Sultanate in particular. Informed by a comparative look at a selection of wider relevant scholarship, we propose to reconsider 15th-century Syro-Egyptian political action within the particular framework of a complex process of state formation. This perspective, defined as ‘Mamlukization’, may help to better account for change, and for contemporary laments that "things aren't what they used to be." In "Part I — Old problems and new trends", we begin by examining the state of the field of 15th-century Mamluk political history, before laying out the new perspective of ‘Mamlukization’ in Part II. Part I explains how Mamluk scholarship has only recently managed to overcome a traditional tendency to view the sultanate's political history as a long process of divergence from an idealized system based on military slavery, raising new difficulties. We conclude that there remains a need to replace this decline paradigm with a more useful conceptual framework. If something profound indeed was taking place in the 15th century, something that is not usefully considered "decline," then what was it?